Investigating the Factors that Influence the Implementation of Virtual Reality in Science Learning - Sumardani, D.; Lin, C. H. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2024)
Advanced virtual reality (VR) holds substantial promise in education and can be seamlessly integrated into classroom instruction, fostering rapid advancements in science education. This research aims to investigate the factors that influence the implementation of VR and the correlation between the technology acceptance model that can lead to its integration in the science educational setting. To address these objectives, structural equation modeling (SEM) is conducted to represent a hypothesis about the causal relationships among factors influencing preservice teachers to implement VR in the classroom, following their engagement in simulated science explorations related to the concept of weightlessness. The results reveal that the proposed model has strong explanatory power in predicting the intention to use VR in the classroom (R2=64.7%). This intention is influenced by perceived usefulness, perceived enjoyment, and the absence of cybersickness. Notably, our findings also indicate that Usage Attitude (UA), which pertains to participants’ positive or negative response towards technological usage, does not mediate the relationship between beliefs (PU, PEU, and PE) and Behavioral Intention (IU), prompting further exploration of the concepts of cognitive and affective attitude. Additionally, the findings from the preservice teachers’ responses support the notion that VR is valuable in educational contexts, enabling immersive experiences, authentic learning, and enhancing the learning journey, along with the concept of learning by doing.